Initial In Vivo Evaluation of a Novel Amikacin-Deoxycholate Hydrophobic Salt Delivers New Insights on Amikacin Partition in Blood and Tissues - Styliani Xiroudaki; Federica Ianni; Samuele Sabbatini; Elena Roselletti; Claudia Monari; Roccaldo Sardella; Anna Vecchiarelli; Stefano Giovagnoli (MDPI AG, 2021)
In this study, an initial in vivo evaluation of a new amikacin-deoxycholate hydrophobic salt aimed at potentiating amikacin action against hard-to-treat lung infections was undertaken by quantifying, for the first time, amikacin in whole blood. Pharmacokinetic evaluation after intranasal administration in a murine model showed higher drug retention in the lungs compared to blood, with no significant differences between the salt and the free drug. Upon repeated administrations, the two treatments resulted in nonsignificant tissue damage and mild higher inflammation for the hydrophobic salt. Whole-blood analysis highlighted an unreported high partition of amikacin in blood components up to 48 h, while significant lung levels were measured up to 72 h. Such a new observation was considered responsible for the nearly overlapping pharmacokinetic profiles of the two treatments. To overcome such an issue, a dry powder in an inhalable form may be best suited. Moreover, if confirmed in humans, and considering the current once-a-day regimen for amikacin aerosols, important yet-to-be-explored clinical implications may be postulated for such amikacin persistence in the organism.